Developing Farm-Level Post-vaccination Sero-Monitoring Systems for H5N1 Highly Pathogenic Avian Influenza in an Endemically Infected Country - Durr, Peter A.; Indriani, Risa; Selleck, Paul; Adjid, Abdul R. M.; Syafriati, Tatty; Ignjatovic, Jagoda (Frontiers in Veterinary Science, 2019)
Whilst the serological responses of poultry following vaccination against highly pathogenic avian influenza H5N1 has been extensively investigated under laboratory conditions, there have been fewer studies conducted in the field. This applies particularly to the endemically infected countries routinely practicing vaccination, where the combination of multiple circulating clades and/or the use of vaccines with different seed strains makes the design and interpretation of field studies especially problematic. To address this for the particular situation of layer hens in the small to medium commercial sector in Indonesia, we developed a sampling regime before and after the vaccination given to point-of-lay pullets, and assessed serological response with a panel of test antigens. This confirmed that high titres were induced in those birds vaccinated with locally produced homologous H5N1 vaccines administered two or more times, but in flocks using imported heterologous H5N2 vaccines median titres were significantly lower, and unlikely to provide protection throughout the production cycle, without additional vaccination. Comparing the HI responses against the panel of antigens enabled the detection of the flock’s exposure to different vaccine antigens, and made possible the detection of mislabelled vaccine seed strains. Furthermore, we show that test antigens need not be exactly matched to assess sero-protection in well vaccinated birds. Finally our study suggests that the POL vaccination serves as a useful reference point for following cohorts of layers throughout their production cycle, and thus enabling robust vaccination field effectiveness studies.